(untitled) (ARQUISUR Revista, 2024)
This article provides an analysis of the urban morphology of Salvador, Bahia (Brazil), focusing on the spatial segregation issues that shape the city. The study examines the physical structure and spatial organization of Salvador, addressing the influence of these factors on the socioeconomic segregation of the city. Also, the configuration of sociospatial segregation is analyzed to study its influence on the relationships among distinct social strata. Based on this premise, we seek to perform a spatial analysis using the software Space Syntax as a tool. Results show how the various configuration patterns and the characterization of socioeconomic sectors reveal an interpretation of the urban morphology of segregation in Salvador.